Analiza sezonske in prostorske spremenljivosti značilnih pretokov rek v Sloveniji - Kostevc, Lea (Acta hydrotechnica, 2022)
The fluctuations between minimum, mean, and high flows in Slovenia are significant, and in recent decades the influence of climate variability is also evident. Due to the lack of precipitation and its uneven temporal and spatial distribution, drought is a growing problem in Slovenia, while on the other hand, the number of extreme flood events is increasing. In the study, the regional diversity and seasonality of characteristic flows, namely mean low (sQnp), mean (sQs), and peak flows (vQvk) from 50 gauging stations are analyzed for the period 1960–2018, applying both an annual and monthly time scale. The ratios between the characteristic flows are calculated, and the results are evaluated both temporally and spatially. The range of values of the ratio vQvk/sQnp varies from about 20 to 1000, while the range of values of the ratio sQs/sQnp is between 2 and 20. Hierarchical clustering of gauging stations for mean low (sQnp) and mean flows (sQs) gave similar results, i.e. gauging stations were clustered into five equal groups in both cases. In the case of hierarchical clustering of gauging stations according to the values of peak flows (vQvk), four groups were formed. However, we can conclude that individual groups are difficult to define spatially in all cases.
Keywords: mean flows; mean low flows; peak flows; prostorska spremenljivost; seasonality; sezonskost; spatial variability; srednji mali pretoki; srednji pretoki; stability; veliki pretoki